Dichorionic diamniotic twin pregnancy complicated by single intrauterine fetal demise secondary to severe early-onset fetal growth restriction: a case report - Naik, Ajay T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Twin pregnancies are associated with increased maternal and perinatal morbidity compared with singleton gestations. Single intrauterine fetal demise (IUFD) complicates a small proportion of twin pregnancies but poses significant diagnostic and management challenges, particularly when it occurs in the second or third trimester. Although adverse outcomes are more commonly reported in monochorionic twins, dichorionic diamniotic (DCDA) pregnancies may also be affected, especially in the presence of severe placental insufficiency and early-onset fetal growth restriction (FGR). A 39-year-old multigravida (Gravida 2) with a history of one prior missed miscarriage conceived a DCDA twin pregnancy following ovulation induction. Early anomaly scans showed structurally normal fetuses. At 22 weeks of gestation, Twin B demonstrated severe early-onset FGR (below the 1st centile), oligohydramnios, and abnormal umbilical artery doppler with absent to reversed end-diastolic flow, suggestive of significant placental insufficiency, while Twin A showed appropriate growth and normal doppler parameters. Despite close antenatal surveillance with serial ultrasonography and doppler studies, follow-up imaging at 26-28 weeks revealed intrauterine fetal demise of Twin B, with ultrasonographic features including spalding sign and marked growth restriction corresponding to 19-20 weeks of gestation. The surviving Twin A remained hemodynamically stable with normal growth and reassuring doppler findings. This case underscores that DCDA twin pregnancies are not immune to severe complications such as single IUFD, particularly in the setting of early-onset FGR and placental insufficiency. Early diagnosis, meticulous fetal and maternal surveillance, and individualized management are essential to optimize outcomes for the surviving twin and ensure maternal safety.